1974
DOI: 10.1002/anie.197404672
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Cycloocta [1,2‐b: 4,3‐b′:5,6‐b″:8,7‐b‴] tetrathiophene

Abstract: fumarate (59.8g, 347 mmol) at room temperature. During the reaction the temperature of the mixture is kept at 35-4OT by water cooling. After stirring for 1 h, all the components that are volatile at 1 lS"C/O.l torr are distilled off to leave 2.1 g of a black viscous residue. Fractional distillation affords 42.7 g of 96 YO pure (GC) diethyl fumarate and 17.Sg of 93.8 % pure (GC) (Zb), b. p. 63-65"C/0.001 torr, which still contains diethyl fumarate (1.6%) and six other unknown compounds (4.6 %).Received: Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There are reports in the literature on cyclooctatetrathiophene (COTh) where thiophene fused with the COT framework 17 . It is also reported that with the presence of electron‐rich thiophene on the boundary and having flexible π‐conjugated skeletons, COTh has prominent applications in optoelectronics 14,17–19 . Considering the connectivity of thiophene, COTh has 15 isomers, and four of them were synthesized and reported by Wang et al 17 The different connectivity of thiophene in synthesized isomers of COTh is confirmed by single‐crystal analysis 20–22 .…”
Section: Introductionmentioning
confidence: 85%
“…There are reports in the literature on cyclooctatetrathiophene (COTh) where thiophene fused with the COT framework 17 . It is also reported that with the presence of electron‐rich thiophene on the boundary and having flexible π‐conjugated skeletons, COTh has prominent applications in optoelectronics 14,17–19 . Considering the connectivity of thiophene, COTh has 15 isomers, and four of them were synthesized and reported by Wang et al 17 The different connectivity of thiophene in synthesized isomers of COTh is confirmed by single‐crystal analysis 20–22 .…”
Section: Introductionmentioning
confidence: 85%
“…The family of COTh s contains many isomers derived from different bithiophenes, such as 5 – 9 (Figure ). As early as 1974, Kauffmann and co‐workers reported the first two isomers of COTh ( 5 and 6 ) in 25 and 23% yields, respectively, and revealed their nonplanar saddle‐shaped geometry (Scheme ) 19. A small amount of 12‐membered macrocyclic compound 34 was afforded as a byproduct (Scheme ) 19b.…”
Section: Intermolecular Cyclizations Of Bithiophene Dicarbanionsmentioning
confidence: 99%
“…As early as 1974, Kauffmann and co‐workers reported the first two isomers of COTh ( 5 and 6 ) in 25 and 23% yields, respectively, and revealed their nonplanar saddle‐shaped geometry (Scheme ) 19. A small amount of 12‐membered macrocyclic compound 34 was afforded as a byproduct (Scheme ) 19b. Iyoda and co‐workers improved the yield for the preparation of 5 and 6 to around 40% yield by transmetalation and replacement of solvents (Scheme ) 20.…”
Section: Intermolecular Cyclizations Of Bithiophene Dicarbanionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrakis(2,3-thienylene) (15)(16)(17) is an interesting ring system in which adjacent thiophene rings are alternatively connected between the α-positions (α, α-linkages) and β-positions (β, β-linkages) (Figure 1). Because of the out-of-plane twisting between the adjacent thiophene rings, these linkages correspond to the chiral axes; both α, α-linkages adopt identical axial chirality but opposite to that of the β, β-linkages, analogously to the linkages in tetraphenylenes (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%